Photo-controllable Resistive Memory Based on Polymer Materials. Issue 1729 (2015) - Dronov, Mikhail; Kotova, Maria; Belogorohov, Ivan
ABSTRACT: We present the memory performance of devices with bistable electrical behavior based on polymer materials. We demonstrate that adding photosensitive particles to admixture allows us to control switching voltages and to observe photo-induced switching in addition to electrical one. From the properties of electrically-induced resistive switching and from the presence of light-induced switching we propose the necessity to consider crossover between to different switching mechanisms – filament formation and charge storage.